Interaction with a Virtual Coach for Active and Healthy Ageing - McTear, Michael; Jokinen, Kristiina; Alam, Mirza Mohtashim; Saleem, Qasid; Napolitano, Giulio; Szczepaniak, Florian; Hariz, Mossaab; Chollet, Gérard; Lohr, Christophe; Boudy, Jérôme; Azimi, Zohre; Roelen, Sonja Dana; et al. (Sensors (Basel, Switzerland), 2023)
Since life expectancy has increased significantly over the past century, society is being forced to discover innovative ways to support active aging and elderly care. The e-VITA project, which receives funding from both the European Union and Japan, is built on a cutting edge method of virtual coaching that focuses on the key areas of active and healthy aging. The requirements for the virtual coach were ascertained through a process of participatory design in workshops, focus groups, and living laboratories in Germany, France, Italy, and Japan. Several use cases were then chosen for development utilising the open-source Rasa framework. The system uses common representations such as Knowledge Bases and Knowledge Graphs to enable the integration of context, subject expertise, and multimodal data, and is available in English, German, French, Italian, and Japanese.